Response from M Maqsood, P Waheed, A Rashid, et al. (J Pak Med Assoc. 2023; 73: 978-982) Aldose reductase gene polymorphism rs752010122 and retinopathy in type 2 diabetics - Muntaha Maqsood; Palvasha Waheed; Amir Rashid; Asifa Majeed; Ahsan Mukhtar (Journal of the Pakistan Medical Association, 2023)
Madam, First of all, I would like to appreciate the reader for their insightful feedback as we can all learn when wisdom is shared. The readers concerns are addressed point by point as follows: 1. Limitations of study • Restriction of funding resources and sample size. • Scarcity of literature regarding available and very limited publication available of the AKR1B1 gene. • Analysis not linked to demographic details, because samples used were de-identified in order to stick to the design of the study.2. The study only discussed the association of AR gene polymorphism rs752010122 and DR regardless of whether the polymorphism was familial or somatic. A family history of diabetic retinopathy (DR) increases its risk in patients with T2DM however it was not the scope of this study. Furthermore, as it was a single centre study with small sample size, including a patient population with diverse ethinicity was not possible. The discussion portion of the article highlights the scarce data available discussing the various AR gene polymorphisms in certain ethincities. However, a large collabrative multicentre study icluding a diverse patient popultaion spanning various demographic areas may be able to identify the association of AR gene polymorphism, ethinicity and DR. 3. The samples were de-identified prior to analysis by multiple blinded researchers. 4. It is acknowledged that the article does not specifically mention that patients with dyslipidaemia were excluded. However, patients with DR suspected secondary to other causes were excluded as mentioned in the “Patient and Methods” section. 5. It is acknowledged that the article does not include how the patients were screened for DR and T2DM, therefore this comment provides us the opportunity to provide those details. Patients were screened for DR by fundoscopy by expert ophthalmolgists at Armed Forces Institute of Ophthalmology. Clinical evaluation icluded BMI, blood pressure and other vital signs. Haematological work up included Fasting Blood Glucose, HbA1c, Fasting Lipid profile, Renal Function Tests, Liver Function Tests and Blood complete Picture. We hope the above satisfies the readers’ concerns. Further feedback is always welcome.